Identification of homogeneous groups of real estate markets and the pandemic resilience of the construction sector - Dąbrowski, Ireneusz; Mach, Łukasz; Mikołajczyk, Łukasz; Kuświk, Arkadiusz (Identyfikacja jednorodnych grup rynków nieruchomości oraz odporność na pandemię sektora budowlanego, 2021)
In the research process, homogeneous groups of voivodeships and the determinants of regional development were identified. The hierarchical method with Ward’s algorithm and the k-means clustering method were employed for two periods, 2015 and 2018. In order to identify the determinants of development, an iterative multidimensional ranking method was used. The results of the research suggested that 16 voivodeships were divided into two groups, in which the leaders with the greatest potential A list of determinants with the highest and lowest dynamics was extracted. A statistical analysis was also performed based on the results of a survey of the economic situation in the construction industry, performed mainly to compare the period before and during the COVID-19 pandemic. The year of 2020, according to the GUS survey, was dominated by pessimism, both in the assessment of barriers to business activity and in the assessment of the current and future situation of enterprises.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 4, s. 32-53
Keywords: clusters analysis; real estate market; rank; potential; pandemic; COVID-19; analiza skupień; rynek nieruchomości; ranking; potencjał; pandemia